The impact of accessibility and service quality on the frequency of patient visits to the primary diabetes care provider: results from a cross-sectional survey performed in six European countries - Uwe Konerding; Tom Bowen; Sylvia G. Elkhuizen; Raquel Faubel; Paul Forte; Eleftheria Karampli; Tomi Malmström; Elpida Pavi; Paulus Torkki (BMC, 2020)
Abstract Background Visits to the primary diabetes care provider play a central role in diabetes care. Therefore, patients should attend their primary diabetes care providers whenever a visit is necessary. Parameters that might affect whether this condition is fulfilled include accessibility (in terms of travel distance and travel time to the practice), as well as aspects of service quality (for example in-practice waiting time and quality of the provider's communication with the patient). The relationships of these variables with the frequency of visits to the primary diabetes care provider are investigated. Methods The investigation is performed with questionnaire data of 1086 type 2 diabetes patients from study regions in England (213), Finland (135), Germany (218), Greece (153), the Netherlands (296) and Spain (71). Data were collected between October 2011 and March 2012. Data were analysed using log-linear Poisson regression models with self-reported numbers of visits in a year to the primary diabetes care provider as the criterion variable. Predictor variables of the core model were: country; gender; age; education; stage of diabetes; heart problems; previous stroke; problems with lower extremities; problems with sight; kidney problems; travel distance and travel time; in-practice waiting time; and quality of communication. To test region-specific characteristics, the interaction between the latter four predictor variables and study region was also investigated. Results When study regions are merged, travel distance and in-practice waiting time have a negative effect, travel time no effect and quality of communication a positive effect on visit frequency (with the latter effect being by far largest). When region specific effects are considered, there are strong interaction effects shown for travel distance, in-practice waiting time and quality of communication. For travel distance, as well as for in-practice waiting time, there are region-specific effects in opposite directions. For quality of communication, there are only differences in the strength with which visit frequency increases with this variable. Conclusions The impact of quality of communication on visit frequency is the largest and is stable across all study regions. Hence, increasing quality of communication seems to be the best approach for increasing visit frequency.